A case of acute liver failure with echovirus infection diagnosed by a multi-virus real-time PCR system. (2021) - Yoshikawa, Yuki; Imamura, Michio; Morio, Kei; Yamaoka, Kenji; Ando, Yuwa; Kosaka, Yumi; Uchikawa, Shinsuke; Fujino, Hatsue; Nakahara, Takashi; Murakami, Eisuke; Yamauchi, Masami; Kawaoka, Tomokazu; et al.
Abstract: Background: Multi-virus real-time polymerase chain reaction (PCR) system is able to simultaneously detect 163 viruses using a multiplex Taqman real-time PCR system. We present a case of acute liver failure (ALF) of unknown etiology diagnosed with echovirus 30 infection via multi-virus real-time PCR. Case presentation: A previously healthy 66-year-old man had a persistent fever and developed ALF of unclear etiology. Although viral infection was suspected, serological screening showed no evidence of acute viral infections such as hepatitis A, B, C and E, Epstein-Barr virus, herpes simplex virus, and varicella zoster virus. Multi-virus real-time PCR revealed the presence of enterovirus and echovirus 30 genomes, and reverse transcription-PCR using enterovirus-specific primers confirmed the presence of enterovirus genome in serum samples at the time of admission. Anti-echovirus antibody titers showed an increase in paired sera. In spite of multimodality treatment, the patient died due to multiple organ failure. Histological analysis in autopsy revealed extensive coagulative necrosis of the hepatocytes and immunohistochemical analysis showed the expression of enterovirus antigens in necrotic hepatocytes. Conclusions: We present here a case of echovirus 30 associated with ALF. Multi-virus real-time PCR is useful for detection of virus for patients with ALF of unknown etiology suspected of harboring a viral infection.